PlGF and sFlt‐1 levels in patients with non‐transfusion‐dependent thalassemia: Correlations with markers of iron burden and endothelial dysfunction. (25th April 2018) - Kelaidi, Charikleia; Kattamis, Antonis; Apostolakou, Filia; Poziopoulos, Christos; Lazaropoulou, Christina; Delaporta, Polyxeni; Kanavaki, Ino; Papassotiriou, Ioannis
Abstract: Background: Levels of the angiogenic cytokines placental growth factor (PlGF) and soluble Fms‐like tyrosine kinase‐1 (sFlt‐1) and the angiogenic balance, expressed by sFlt‐1/PlGF ratio, are perturbed in sickle‐cell disease and iron overload, but they have not been evaluated in non‐transfusion‐dependent thalassemia (NTDT). Patients and Methods: We measured levels of PlGF, sFlt‐1 and vWF:antigen in patients with NTDT of beta‐thalassemia genotype, and correlated them with erythrocytic indices and markers of iron overload, inflammation, and tissue hypoxia. Thirty‐four NTDT patients with mean hemoglobin level of 8.4 g/dL were included in the study along with 20 apparently healthy individuals who served as controls. Results: Ferritin, LDH, and hs‐CRP were higher in patients as compared to controls. We found significant differences between patients and controls in regard to levels of PlGF (52.2 vs 17.2 pg/mL, P  < .001), sFlt‐1/PlGF (2 vs 4.7, P  < .001), and vWF:antigen (88 vs 77.1 IU/dL, P  < .01). There was a strong correlation of ferritin with PlGF ( r  = .653, P  < .001) and with vWF:antigen ( r  = .503, P  = .003). Conclusions: In this study, we demonstrated an association between increased PlGF and iron overload and the degree of tissue hypoxia in patients with NTDT. High vWF:antigen expressing endothelial damage may be associated with specific NTDT comorbidities.